Selected Papers from IIKII 2019 conferences in Symmetry - Meen, Teen-Hang; Tijus, Charles; Tu, Jih-Fu (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The International Institute of Knowledge Innovation and Invention (IIKII, http://www.iikii.org) promotes the exchange of innovations and inventions and establishes a communication platform for international innovations and research. In 2019, IIKII cooperates with the IEEE Tainan Section Sensors Council to hold IEEE conferences, such as IEEE ICIASE 2019, IEEE ECBIOS 2019, IEEE ICKII 2019, ICUSA-GAME 2019, and IEEE ECICE 2019. This Special Issue, entitled "Selected Papers from IIKII 2019 conferences", aims to showcase outstanding papers from IIKII 2019 conferences, including symmetry in physics, chemistry, biology, mathematics, and computer science, etc. It selected 21 outstanding papers from 750 papers presented in IIKII 2019 conferences on the topic of symmetry. The main goals of this Special Issue are to encourage scientists to publish their experimental and theoretical results in as much detail as possible, and to discover new scientific knowledge relevant to the topic of symmetry.